Sustainability of health information systems: a three-country qualitative study in southern Africa. Issue 1 (December 2017) - Moucheraud, Corrina; Schwitters, Amee; Boudreaux, Chantelle; Giles, Denise; Kilmarx, Peter; Ntolo, Ntolo; Bangani, Zwashe; St. Louis, Michael; Bossert, Thomas
Abstract Background Health information systems are central to strong health systems. They assist with patient and program management, quality improvement, disease surveillance, and strategic use of information. Many donors have worked to improve health information systems, particularly by supporting the introduction of electronic health information systems (EHIS), which are considered more responsive and more efficient than older, paper-based systems. As many donor-driven programs are increasing their focus on country ownership, sustainability of these investments is a key concern. This analysis explores the potential sustainability of EHIS investments in Malawi, Zambia and Zimbabwe, originally supported by the United States President's Emergency Plan for AIDS Relief (PEPFAR). Methods Using a framework based on sustainability theories from the health systems literature, this analysis employs a qualitative case study methodology to highlight factors that may increase the likelihood that donor-supported initiatives will continue after the original support is modified or ends. Results Findings highlight commonalities around possible determinants of sustainability. The study found that there is great optimism about the potential for EHIS, but the perceived risks may result in hesitancy to transition completely and parallel use of paper-based systems. Full stakeholder engagement is likely to be crucial for sustainability, as well as integration with other activities within the health system and those funded by development partners. The literature suggests that a sustainable system has clearly-defined goals around which stakeholders can rally, but this has not been achieved in the systems studied. The study also found that technical resource constraints – affecting system usage, maintenance, upgrades and repairs – may limit EHIS sustainability even if these other pillars were addressed. Conclusions The sustainability of EHIS faces many challenges, which could be addressed through systems' technical design, stakeholder coordination, and the building of organizational capacity to maintain and enhance such systems. All of this requires time and attention, but is likely to enhance long-term outcomes.